The Phenomenon of Palestinian Postcolonial Novel and Short Novel in Arabic Literature - Karić, Dženita (Prilozi za orijentalnu filologiju, 2017)
In this paper the focus is on the validity of the application of the postcolonial theory onto the chosen corpus from the modern Palestinian literature. In that process, Palestinian literature is being placed into the larger framework of the modern Arabic literature, and the special emphasis is put on the turning points in the development of the Arabic postcolonial literature, that is on the years 1948 and 1967. The paper finally deals with the specific character of Palestinian postcolonial novel in the Arabic literature, and pinpoints its artistic potential and openness to the diverse critical approaches.